a2-4a-43=2

Move 2 to the left side of the equation by subtracting it from both sides.

a2-4a-43-2=0

Subtract 2 from -43.

a2-4a-45=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -45 and whose sum is -4.

-9,5

Write the factored form using these integers.

(a-9)(a+5)=0

(a-9)(a+5)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

a-9=0

a+5=0

Set the first factor equal to 0.

a-9=0

Add 9 to both sides of the equation.

a=9

a=9

Set the next factor equal to 0.

a+5=0

Subtract 5 from both sides of the equation.

a=-5

a=-5

The final solution is all the values that make (a-9)(a+5)=0 true.

a=9,-5

Solve for a a^2-4a-43=2